The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/bdra.20360
|View full text |Cite
|
Sign up to set email alerts
|

Health care expenditures of children and adults with spina bifida in a privately insured U.S. population

Abstract: Although per capita medical care utilization and expenditures are highest among children, adults constitute an important and growing share of the population living with spina bifida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 12 publications
(12 reference statements)
5
115
1
1
Order By: Relevance
“…The disease is associated not only with early mortality [14], but also with greater need for health care services, in particular during the first years of life. In general, children aged from 1 to 17 years had 13 times higher medical expenditures than non-spina bifida children [15].…”
Section: Timely Supplementation Of Folate Prevents Birth Defectsmentioning
confidence: 93%
“…The disease is associated not only with early mortality [14], but also with greater need for health care services, in particular during the first years of life. In general, children aged from 1 to 17 years had 13 times higher medical expenditures than non-spina bifida children [15].…”
Section: Timely Supplementation Of Folate Prevents Birth Defectsmentioning
confidence: 93%
“…Total lifetime cost of a person with SB was estimated at $635,763 (in 2001-2003 $), with total direct costs of $279,210, and indirect costs of $356,553 (work productivity loss due to heightened morbidity and premature mortality). 4 Caregivers of children with SB worked an annual average of 7.5 to 11.3 hours less per week depending on the disability severity, which translated to lifetime costs of $133,755 in 2002 $. 7 Other studies have reported costs of US$294,000 per infant.…”
Section: -7mentioning
confidence: 99%
“…2 US incidence rates for SB range from 3 to 6 cases per 10,000 live births. 3,4 Infants with a NTD tend to have severe and life-long disabilities, and face the risk of psychosocial maladjustment. 5 Most are unable to function independently as adults, with common disabilities and medical problems including sight problems, dysfunction in the arms, epilepsy, bowel and bladder dysfunction.…”
mentioning
confidence: 99%
“…10 Adults with myelomeningocele now account for greater health care expenditures and more hospital admissions than children with this condition. 66 Another factor impinging on the survival of newborns during this epoch was variation in criteria for treatment. A complete discussion of the historic controversy over selection of patients for active treatment is beyond the scope of this review, but understanding of contemporary survival statistics requires a minimum of context.…”
Section: Survivalmentioning
confidence: 99%